2015
DOI: 10.1063/1.4917192
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: The Hash House Harriers and the winding path to materials discovery

Abstract: Materials science research can be both very demanding and extremely rewarding. In this Commentary, in my own research of new electronic and magnetic materials, I give numerous exemplars of the path followed to materials discovery. I also highlight the parallels between my research experiences with the pastime of running. I hope that my thoughts will help guide junior researchers along the often tortuous and exciting path to new materials and that I can teach them to be open minded and persistent about followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…That is a highly admirable skill. The successful NMP research effort combines skills found in professional fishermen, [91] master chefs, [137] and trackers or explorers [138]. These are key parts of what we do and key parts of what we need the public and funding agencies to understand, appreciate and support.…”
Section: [25] [26] [32] [33] [52] [60] [75] [92]mentioning
confidence: 99%
“…That is a highly admirable skill. The successful NMP research effort combines skills found in professional fishermen, [91] master chefs, [137] and trackers or explorers [138]. These are key parts of what we do and key parts of what we need the public and funding agencies to understand, appreciate and support.…”
Section: [25] [26] [32] [33] [52] [60] [75] [92]mentioning
confidence: 99%